2021
DOI: 10.3390/ph14080778
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Correlations between the Expression of Histopathological Ubiquitin-Conjugating Enzyme 2O Staining and Prostate Cancer Advancement

Abstract: Background: The mTOR signaling pathway is inactivated by AMPK’s tumor-suppressing function. It is recognized that ubiquitin conjugating enzyme 2O (UBE2O), which directly targets AMPK for ubiquitination and degradation, is intensified in human cancers. Methods: This study investigated the clinical data about prostate cancer. Examination was also carried out into tissue microarrays (TMA) of human prostate cancer (n = 382) and adjacent non-neoplastic tissues around prostate cancer (n = 61). The TMA slides were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…UBE2O promotes the proliferation, EMT, and stemness properties of breast cancer cells through the UBE2O/AMPKalpha2/mTORC1-MYC positive feedback loop ( 29 ). A positive correlation was reported between the expression of histopathological UBE2O staining and prostate cancer advancement ( 30 ). UBE2O promotes hepatocellular carcinoma cell proliferation and invasion by regulating the AMPK/mTOR pathway ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…UBE2O promotes the proliferation, EMT, and stemness properties of breast cancer cells through the UBE2O/AMPKalpha2/mTORC1-MYC positive feedback loop ( 29 ). A positive correlation was reported between the expression of histopathological UBE2O staining and prostate cancer advancement ( 30 ). UBE2O promotes hepatocellular carcinoma cell proliferation and invasion by regulating the AMPK/mTOR pathway ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…UBE2O, an E2/E3 hybrid enzyme, can modulate its substrate through mono-ubiquitination, multisite mono-ubiquitination, or polyubiquitination ( 50 , 57 , 58 ). Previous studies have shown that UBE2O plays an oncogenic role in diverse cancers, such as breast cancer ( 59 ), prostate cancer ( 60 ), liver cancer ( 61 ), and lung cancer ( 52 ), etc. However, Xu et al.…”
Section: Discussionmentioning
confidence: 99%